Exploring effective teaching methods for physical education in secondary school classrooms - Ahmad Kamal, Azlan; Samsuddin, Muhamad Ikhwan (Faculty of Sports Science and Recreation, 2025)
Teaching method is an approach used in teaching and A well-strategised teaching method can improve the class atmosphere, student knowledge, and lesson experience. The objective of this research being held to study the effectiveness of physical education teaching method inside the classroom, the student’s experience during learning process and find the differences between the teaching method used for students of different genders. The impact of using a suitable teaching method, especially during weather changes, will be interesting to students in learning Physical Education (PE) inside the confines of a classroom. This is important in tropical countries like Malaysia, where the weather can be volatile. The present study employed a quantitative research method to collect and analyse data. The data were collected from 174 randomly selected Form 3 to Form 5 students from a secondary school in an urban area in Selangor. A questionnaire was used to collect data from the sample. This data was used to identify the teaching method used by the teachers and the students' learning experience during PE lessons conducted inside the classroom. The data analysis revealed a significant relationship between the teaching method used by the teacher and students' learning experience during PE lessons inside the classroom. It was found that using various teaching approaches in the classroom will lead to a more effective learning experience among students. In addition, there is no significant difference in teaching methods used for students across genders. In conclusion, the teaching method used to teach physical education is differ by the students’ gender due to gender interest in learning different ways of learning physical education.